PENGARUH PELATIHAN DAN KEDISIPLINAN TERHADAP PRODUKTIVITAS KERJA PERAWAT PNS PADA RUMAH SAKIT UMUM DAERAH LUBUK SIKAPING - Yurasti Yurasti; Ria Widhia Sari; Yulihardi Yulihardi; Bayu Syahputra (JURNAL ILMIAH EDUNOMIKA, 2022)
This research aims to test the influence of training and discipline on the productivity of civil servant nurses of Lubuk Sikaping Regional General Hospital with total population of 98 people. The study sample used saturated sampling techniques. Research data is collected by method and analyzed with multiple linear regressions. The results of the first hypothesis test study showed that the sig value of 0,000 < alpha 0.05 so that training had an effect on the work productivity of civil servant nurses of Lubuk Sikaping Regional General Hospital. The results of the second hypothesis test showed that the sig value of 0.019 < alpha 0.05 so that discipline had an influence on the productivity of civil servant nurses of Lubuk Sikaping Regional General Hospital. The results of the third hypothesis test showed that the sig value of 0.000 < alpha 0.05 so that training and discipline together had an influence on the productivity of civil servant nurses of Lubuk Sikaping Regional General Hospital. Keywords: Training, Discipline and Work Productivity